The large GTPase Mx1 binds Kif5B for cargo transport along microtubules. (23rd October 2018) - Ringer, Karina; Riehl, Jana; Müller, Manuel; Dewes, Jenny; Hoff, Florian; Jacob, Ralf
Abstract : A highly specific transport and sorting machinery directing secretory cargo to the apical or basolateral plasma membrane maintains the characteristic polarized architecture of epithelial cells. This machinery comprises a defined set of transport carriers, which are crucial for cargo delivery to the correct membrane domain. Each carrier is composed of a distinct set of proteins to verify precise routing and cargo selection. Among these components, the dynamin‐related GTPase Mx1 was identified on post‐Golgi vesicles destined for the apical membrane of MDCK cells. In addition to the presence on late secretory compartments, Mx1 was also detected on compartments of the early secretory pathway. Vesicular structures positive for this GTPase are highly dynamic, and we have studied the influence of the microtubule cytoskeleton on this motility. Live‐cell microscopy indicated that microtubule disruption using nocodazole inhibits long‐range trafficking of these structures. Mx1 directly or indirectly interacts with α‐tubulin and the kinesin motor Kif5B as assessed by coimmunoprecipitation. In agreement with these observations knock out of Mx1 or a mutation in the unstructured L4 loop of Mx1 decreases the efficiency of apical cargo delivery. Interestingly, the L4 loop mutant still interacts with Kif5B; however, it causes vesicle elongation. This suggests that Mx1 aids in vesicle fission and stabilizes the interaction between Kif5B, microtubules and apical transport carriers. Abstract : The GTPase Mx1 aids in vesicle fission and stabilizes the interaction of the kinesin motor Kif5B with apical transport vesicles.